SUPLEMENTASI KELAPA KOPYOR TERHADAP AKTIVITAS SUPEROKSIDA DISMUTASE DAN PATOLOGI ANATOMI HATI TIKUS AKIBAT PERLAKUAN PARASETAMOL - Endang Zainal Hasan, Akhmad; Hasim, Hasim; Setiyono, Agus; Winahyu Ariadini, Sekar (FITOFARMAKA | Jurnal Ilmiah Farmasi, 2013)
This research aimed at determining of the effects of the induction of paracetamoland kopyor coconut on the activity of superoxide dismutase (SOD) and pathologicanatomy of rat’s liver. Previous research shows that paracetamol caused negative effect to the body while kopyor coconut has the ability to improve human health, related to its capacity to prevent oxidative damage of human body. In this research, the positive effect of kopyor is approached through measurement of body weight and the activity of the total SOD enzyme of animals tested, which are induced by paracetamol and fed with kopyor. Rat’s administered with temulawak were positive control. The result showed that paracetamol treatment using toxic dose was found to reduce body weight of tested animals. Meanwhile, both kopyor and temulawak supplements were able to counter the negative effect of paracetamol, indicated by the increase in the body weight of tested animals. Other results showed that treatments with temulawak and 5 times-dose of kopyor supplement demonstrated a significantly high total SOD activity in the liver as compared to negative control. Furthermore, pathologic observation of the tested animals’ liver showed that 5 time-dose of kopyor treatment was confirmed to improve the recovery of the liver caused by negative effect of paracetamol, better than the negative control.Key words: kopyor coconut, superoxide dismutase, free radical, pathologic